COVID-19 Pandemic: Opportunity for a True Economic and Regional Integration of Africa - Modeste Ndaba Modeawi; Clarisse Falanga Mawi; Urbain Mazo Nyante; Jacquie Kangu Kobe; Ruphin Djolu Djoza; JP Mokombe Magbukudua; Masengo Ashande Colette; Gédéon Ngiala Bongo; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua (Budapest International Research and Critics University, 2021)
According to official sources, the coronavirus pandemic that emerged in China in December 2019 has already infected more than 17 million and killed more than 666,850 people. Less impacted than the rest of the world, the Africa continent has nearly 890,000 confirmed cases as of July 30, 2020. According to the African Bank of Development, nearly 50 million Africans will be victims of extreme poverty as a result of the coronavirus pandemic; and this, following the global economic crisis due to this pandemic. It is shown that between 2020 and 2021, Africa will lose in terms of economic income ¼ of trillion dollars and that a contraction of 3.4% of GDP would be noticed. The risk of decline is justified by the decline in oil production by the main exporting countries, notably Algeria, Nigeria and Angola; in addition to the decline in commodity prices on the world market, the volatility of global financial conditions and natural disasters. Even if some analysts believe that the effects of this pandemic are temporary on the economy of the states, it is clear to note that they are perceptible on the world economy in general. In Africa, the low rate of infection, which is 5% since the emergence of the pandemic until July 30, 2020, is a favorable opportunity for the continent to recover and accelerate the process of its economic and regional integration.